2021
DOI: 10.1093/g3journal/jkab305
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene expression dynamics in germ line and somatic tissue during ovariole morphogenesis in Drosophila melanogaster

Abstract: The survival and evolution of a species is a function of the number of offspring it can produce. In insects the number of eggs that an ovary can produce is a major determinant of reproductive capacity. Insect ovaries are made up of tubular egg-producing subunits called ovarioles, whose number largely determines the number of eggs that can be potentially laid. Ovariole number is directly determined by the number of cellular structures called terminal filaments, which are stacks of cells that assemble in the lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(42 citation statements)
references
References 85 publications
4
38
0
Order By: Relevance
“…S2), which may facilitate the observed adaptive evolution of the protein sequences (Otto 2004; Mank and Ellegren 2009; Whittle et al 2021). In sum, these five genes were identified independently from two distinct expression datasets (Slaidina et al 2020; Tarikere et al 2022), were upregulated in two of the most crucial cell types for ovariole number determination namely TFs and SH cells (table S5, table 4), and exhibited rapid protein changes, positive selection, and narrow expression breadth (table 4). Thus, multiple lines of evidence point towards these genes as having a central role in the interspecies divergence of ovariole number.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2), which may facilitate the observed adaptive evolution of the protein sequences (Otto 2004; Mank and Ellegren 2009; Whittle et al 2021). In sum, these five genes were identified independently from two distinct expression datasets (Slaidina et al 2020; Tarikere et al 2022), were upregulated in two of the most crucial cell types for ovariole number determination namely TFs and SH cells (table S5, table 4), and exhibited rapid protein changes, positive selection, and narrow expression breadth (table 4). Thus, multiple lines of evidence point towards these genes as having a central role in the interspecies divergence of ovariole number.…”
Section: Resultsmentioning
confidence: 99%
“…The melanogaster subgroup had the following advantages for our study: (1) each species has a well-annotated whole genome sequence available (Gramates et al 2022); (2) the clade exhibits substantial variation in ovariole numbers among species, typically about 39.2 (per female) for D. melanogaster and 17.0 for D. sechellia and intermediate values for D. simulans (33.9), D. yakuba (25.8) and D. erecta (27.0) (fig. 2; see values and mild variability (Hodin and Riddiford 2000; Starmer et al 2003; Markow et al 2009); (3) the close relatedness of the five species (Tamura et al 2004; Cutter 2008) minimizes biological differences other than ovariole numbers among taxa, a feature that facilitates detection of cause-effect relationships (here, dN/dS and ovariole number (Felsenstein 1985; Bromham et al 1996; Whittle and Johnston 2003; Thomas et al 2010); (4) the taxa have known high confidence orthologs (Waterhouse et al 2011; Gramates et al 2022) and previously calculated M0 dN/dS values (M0 is a single value per phylogeny) per gene from PAML (Yang 1997, 2007; Stanley and Kulathinal 2016), as well as five-species codon alignments per gene available for customized dN/dS analysis (Stanley and Kulathinal 2016); (5) the dN and dS values among the species in this subgroup have substantially diverged, yet are also unsaturated in the frequency of substitutions, and thus are within the ideal range for dN/dS analysis (Castillo-Davis et al 2004; Larracuente et al 2008; Treangen and Rocha 2011) (for example, we found that the 95 th percentile for M0 dN=0.235 and M0 dS=0.791 for the 9,232 genes that had orthologs in all five species and M0 values) and; (6) all species in the clade are very closely related to D. melanogaster , the species for which experimental and transcriptome data on genes associated with ovariole roles are available (Kumar et al 2020; Slaidina et al 2020; Tarikere et al 2022). In sum, this taxonomic group is especially well suited to the study of the evolution of ovariole-related genes.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Yang et al identified the miRNAs that are differentially expressed in the Drosha mutant [ 60 ], including let-7, miR-2, miR-8, miR-14, miR-33, miR-125, miR-184, and miR-277. Nevertheless, the differentially expressed genes in the germline of ovariole morphogenesis have been identified by Tarikere et al [ 108 ]. The target genes of the mentioned miRNAs may be differentially expressed and identified for future studies.…”
Section: Micrornas In Drosophilamentioning
confidence: 99%
“…Although eggpl expression has been detected in other genomic studies of the ovary (Rust et al, 2020a;Tarikere et al, 2022), to our knowledge, this is the first study to investigate the eggpl expression pattern in vivo and the phenotype of eggpl mutants. It remains unclear how eggpl regulates oogenesis downstream of insulin signaling, but its similarity to mucins raises the interesting possibility that it may function as a cell signaling component (Singh & Hollingsworth, 2006).…”
mentioning
confidence: 94%